2005
DOI: 10.1088/0031-9155/50/15/001
|View full text |Cite
|
Sign up to set email alerts
|

Scanning path optimization for ultrasound surgery

Abstract: One of the problems in ultrasound surgery is the long treatment times when large tumour volumes are sonicated. Large tumours are usually treated by scanning the tumour volume using a sequence of individual focus points. During the scanning, it is possible that surrounding healthy tissue suffers from undesired temperature rise. The selection of the scanning path so that the tumour volume is treated as fast as possible while temperature rise in healthy tissue is minimized would increase the efficiency of ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…We used the optimal control approach described in [1] but it was applied to the trajectory of the focal spot during a pulse. The algorithm is briefly summarized here for the considered equations.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the optimal control approach described in [1] but it was applied to the trajectory of the focal spot during a pulse. The algorithm is briefly summarized here for the considered equations.…”
Section: Definitionsmentioning
confidence: 99%
“…Several strategies have been reported to achieve this goal, based on MRI monitoring [1], optimization of pulse arrangement [2], optimization of the duty cycle [3] or multiple focusing with phased array [4]. These strategies aim at maximizing thermal build-up while maintaining pre-focal heating at an acceptable level and avoiding overtreatment, which, from our viewpoint, is a waste of energy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Mougenot et al [15] demonstrated that by mechanically scanning single focal pattern with a multi-spiral trajectory was also capable of producing large thermal lesion with the cross sectional diameter ranging 9-19 mm. Malinen et al [16] in their theoretical study also showed that by scanning the focal beam pattern was capable of producing 3D sphere-shaped thermal lesion (20 mm in diameter) in breast model. The aforementioned studies supported that scanning type technique is a useful and effective strategy for large tumor treatment and possibly achieve the requirement to reach satisfactory treatment conformability and treatment time.…”
Section: Introductionmentioning
confidence: 97%
“…Because of thermal diffusion from the nearby treated region, the lesion size of each treatment spot will gradually become larger as the HIFU therapy progresses (Curiel et al 2004), which may cause insufficient treatment of the initial spots and over-treatment of those later ones. A scanning path optimization method was developed to treat the tumor volume as fast as possible while keeping the temperature in the healthy tissue within a safe threshold (42 C) based on the minimum time formulation from optimal control theory (Malinen et al 2005). Large numbers of phased array elements (530) and foci in the target (300 for a sphere with radius of 1.9 cm) are required in the theoretical simulation, but these are unattainable for most commercially available HIFU systems.…”
Section: Introductionmentioning
confidence: 99%